Backing up digital preservation practice with empirical research: The National Library of Australia's Digital Preservation Knowledge Base. Issue 2 (August 2017) - Kay, Gareth; Coufal, Libor; Pearson, Mark
This article introduces the National Library of Australia's Digital Preservation Knowledge Base which helps the Library to manage digital objects from its collections over the long term. The Knowledge Base includes information on file formats, rendering software, operating systems, hardware and, most importantly, the relationships between them. Most of the work on the Knowledge Base over the last few years has been focused on the mapping of functional relationships between file formats, their versions and software applications. The information is gathered through unique empirical research and is initially being recorded in a multiple-worksheet Excel file in a semi-structured format, though development of a prototype graph database is underway.